New Digital Paradigm and Motherhood in Migratory Contexts - Ortiz Cobo, Mónica; Jeri Levano, Renzo Ismael; García Martín, José (Journal of Education Culture and Society, 2024)
Aim. The present study aims to explore the maternal role of migrants in pre-digital and digital contexts. For this purpose, the study analyses the relationships among migrant mothers in digital and pre-digital contexts and the impact of their mother-child relationship. Methods. Virtual ethnography has enabled the analysis of various heterogeneous moments and contexts, as well as a virtual exploration of the social networks of the twenty-four participants in this study. Meanwhile, multi-sited ethnography has allowed access to and the utilization of multiple interconnected spaces in migratory contexts. Results. The inclusion of digital technology, the use of social networks, and the polymedia environment enable migrant mothers to challenge geographical and temporal barriers and devise strategies that allow them to maintain their mother-child relationship through ubiquitous and real-time transnational communication. This distinguishes them from migrant mothers of the pre-digital era, whose maternal roles were threatened by physical distance and the limited availability, at that time, of communication tools. Conclusion. A new digital paradigm has enabled the construction of digital motherhood in migratory contexts, representing a significant evolution in parental dynamics affecting 21st-century mothers, often referred to as "digital natives". This technological shift has altered the traditional conception of motherhood and long-distance caregiving. Changes in family relationships redefine the migratory experience and motherhood, as well as influence processes of identity, belonging, and adaptation in virtual contexts.